Analysis Of Violence Racism In Jordan Peele’s Get Out - Purba, Parlindungan; Genapinna, Mericci; Pohan, Riko Andika Rahmat (Politeknik Harapan Bangsa Surakarta, 2022)
The objective of this study is to find out the violent racism and the process of the main character getting out from the violent racism portrayed in a movie entitled Get Out by Jordan Peele. There are three forms of violence and racism that appeared in the movie according to Johan Galtung journal (1969) such as direct, structural, and cultural. In order to get the objective of the study, the researcher uses the theory of racism and violence with a descriptive qualitative method by Robert K.Yin. Forms of violence and racism are explained in the dialogue and scenes from the movie. In analyzing the object of the study, there are four techniques that are cooperated in finding and collecting data. They are watching, making notes, identifying, and the last classifying the data. The result of this study is to find out the violence of racism which is classified into three forms such as direct, structural, and cultural violence, and also to describe the process of how the main character escapes the violence of racism. Keywords: Movie, Racism, Violence, Violence Racism